Palbociclib for residual high-risk invasive HR-positive and HER2-negative early breast cancer: the Penelope-B trial - Loibl, Sibylle; Marmé, Frederik; Martin, Miguel; Untch, Michael; Bonnefoi, Hervé; Kim, Sung-Bae; Bear, Harry; McCarthy, Nicole; Melé Olivé, Mireia; Gelmon, Karen; García-Sáenz, José; Kelly, Catherine M.; et al. (Journal of clinical oncology, 2021)
PURPOSE - - About one third of patients with hormone receptor-positive, human epidermal growth factor receptor 2-negative breast cancer who have residual invasive disease after neoadjuvant chemotherapy (NACT) will relapse. Thus, additional therapy is needed. Palbociclib is a cyclin-dependent kinase 4 and 6 inhibitor demonstrating efficacy in the metastatic setting. - - PATIENTS AND METHODS - - PENELOPE-B (NCT01864746) is a double-blind, placebo‐controlled, phase III study in women with hormone receptor-positive, human epidermal growth factor receptor 2-negative primary breast cancer without a pathological complete response after taxane‐containing NACT and at high risk of relapse (clinical pathological staging-estrogen receptor grading score ≥ 3 or 2 and ypN+). Patients were randomly assigned (1:1) to receive 13 cycles of palbociclib 125 mg once daily or placebo on days 1-21 in a 28-day cycle in addition to endocrine therapy (ET). Primary end point is invasive disease-free survival (iDFS). Final analysis was planned after 290 iDFS events with a two-sided efficacy boundary P < .0463 because of two interim analyses. - - RESULTS - - One thousand two hundred fifty patients were randomly assigned. The median age was 49.0 years (range, 19-79), and the majority were ypN+ with Ki-67 ≤ 15%; 59.4% of patients had a clinical pathological staging-estrogen receptor grading score ≥ 3. 50.1% received aromatase inhibitor, and 33% of premenopausal women received a luteinizing hormone releasing hormone analog in addition to either tamoxifen or an aromatase inhibitor. After a median follow-up of 42.8 months (92% complete), 308 events were confirmed. Palbociclib did not improve iDFS versus placebo added to ET-stratified hazard ratio, 0.93 (95% repeated CI, 0.74 to 1.17) and two-sided weighted log-rank test (Cui, Hung, and Wang) P = .525. There was no difference among the subgroups. Most common related serious adverse events were infections and vascular disorders in 113 (9.1%) patients with no difference between the treatment arms. Eight fatal serious adverse events (two palbociclib and six placebo) were reported. - - CONCLUSION - - Palbociclib for 1 year in addition to ET did not improve iDFS in women with residual invasive disease after NACT.